2004
DOI: 10.1007/s10789-005-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical methods of enhancing the performance of high-Tc superconductors

Abstract: Experimental data are summarized on the optimization of the performance of YBa 2 Cu 3 O 7x , Bi 2 Sr 2 CaCu 2 O 8 + δ , and (Bi,Pb) 2 Sr 2 Ca 2 Cu 3 O 10 + δ high-T c ceramics by producing structural defects via irradiation or doping with metals and different inorganic compounds. A classification of additions is proposed according to their interaction with the superconductors. For additions having an advantageous effect on the superconducting and mechanical properties of the high-T c materials, the optimum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…A similar effect is observed when impurity defects are incorporated into HTSC. Namely, both initial growth and subsequent drop of the critical current are not accompanied by noticeable change of T c either [1]. Hence, to make clear the physical reason of non-monotonous behaviour of the HTSC critical current dependence on the concentration of defects, and to reveal why the critical current decreases as the concentration of defects increases are of importance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect is observed when impurity defects are incorporated into HTSC. Namely, both initial growth and subsequent drop of the critical current are not accompanied by noticeable change of T c either [1]. Hence, to make clear the physical reason of non-monotonous behaviour of the HTSC critical current dependence on the concentration of defects, and to reveal why the critical current decreases as the concentration of defects increases are of importance.…”
mentioning
confidence: 99%
“…Both chemical impurities [1] and radiation-induced defects caused by irradiation of HTSC with various types of particles [2][3][4][5] can act as additional structural defects. The phenomenon of j c increasing is particularly strong when samples with low concentrations of defects, e.g., single crystals are irradiated.…”
mentioning
confidence: 99%
“…Such impurities should be chosen so that they, on the one hand, would not decrease the critical temperature of the initial superconductor and, on the other hand, play the role of effective pinning centers when incorporated introduced into a superconducting material. Investigations on introduction of nanoadditives of magnesium oxide; niobium, tantalum, titanium, and silicon carbides; and hafnium nitride into HTSC materials have been performed [1]. The results obtained showed that the critical current density in HTSC compounds (Bi,Pb) 2 Sr 2 CaCu 2 O 8 + x (Bi2212) and (Bi,Pb) 2 Sr 2 Ca 2 Cu 3 O 10 + x (Bi2223) can be increased [1,2].…”
mentioning
confidence: 99%
“…Investigations on introduction of nanoadditives of magnesium oxide; niobium, tantalum, titanium, and silicon carbides; and hafnium nitride into HTSC materials have been performed [1]. The results obtained showed that the critical current density in HTSC compounds (Bi,Pb) 2 Sr 2 CaCu 2 O 8 + x (Bi2212) and (Bi,Pb) 2 Sr 2 Ca 2 Cu 3 O 10 + x (Bi2223) can be increased [1,2].…”
mentioning
confidence: 99%